'Dos and don'ts' in the management of hyponatremia. (2nd September 2015) - Aylwin, Simon; Burst, Volker; Peri, Alessandro; Runkle, Isabelle; Thatcher, Nicholas
Abstract: Introduction and objective: The management of hyponatremia has evolved in recent years, particularly with the introduction of tolvaptan for hyponatremia secondary to the syndrome of inappropriate antidiuretic hormone secretion (SIADH). This commentary presents a summary of recent international recommendations in the form of a series of didactic 'dos and don'ts', in order to provide concise, practical guidance for practising clinicians focused on the investigation and management of euvolemic hyponatremia (SIADH). Research methods: A multidisciplinary group of international experts reviewed existing guidelines and the evidence cited within to summarize the recommendations in a practical method for use in clinical practice. Recommendations: The 'dos and don'ts' are presented under topic headings that include diagnosis and diagnostic tests, specific causes, correction of acute hyponatremia, correction rates for chronic hyponatremia, management of SIADH including fluid restriction, hypertonic saline and pharmacological strategies, and management of overcorrection. Within each topic, the authors summarize the published recommendations on managing hyponatremia and the use of specific agents for the treatment of SIADH. Conclusion: Practising clinicians can use these 'dos and don'ts' to provide clear, up-to-date guidance on how to manage hyponatremia and the use of tolvaptan in SIADH.